Self-employment and Health: Barriers or Benefits? - Cornelius A. Rietveld; Hans van Kippersluis; A. Roy Thurik (Tinbergen Institute, 2013)
The self-employed are often reported to be healthier than wage workers; however, the cause of this health difference is largely unknown. The longitudinal nature of the US Health and Retirement Study allows us to gauge the plausibility of two competing explanations for this difference: a contextual, causal effect of self-employment on health (benefit effect), or a health-related selection of individuals into self-employment (barrier effect). Our main finding is that the selection of comparatively healthier individuals into self-employment accounts for the positive cross-sectional difference. The results rule out a positive contextual effect of self-employment on health, and we present tentative evidence that, if anything, engaging in self-employment is bad for one's health. Given the importance of the self-employed in the economy, these findings contribute to our understanding of the vitality of the labor force.
Keywords: I19; L26; 330; Health; HRS; selection; self-employment